Effect of fertilization and inoculation with native rhizobial strains on growth of Prosopis alba seedlings under nursery conditions - Salto, Carla Susana; Melchiorre, Mariana; Oberschelp, Gustavo Pedro Javier; Pozzi, Ezequiel; Harrand, Leonel (2018)
Prosopis alba (algarrobo blanco) is able to fix N2 symbiotically associated with nodule inducing rhizobacteria. However, there is no information related to the effects and interactions of inoculation and fertilization during the production of “algarrobo blanco” seedlings. The aim of this work was to evaluate, under nursery conditions, the combined effect of inoculation with specific rhizobacteria and nitrate (NO3 −) levels on growth and nodulation of P. alba seedlings from two localities and phytogeographical provenances: La Paz and Campo Durán from Espinal and Parque Chaqueño regions, respectively. Seeds were inoculated two days after sowing with a mix containing three specific rhizobacteria isolates and fertilized with three NO3 − concentrations (0, 2.8 and 21.6 mM). Inoculation combined with 2.8 mM NO3 − increased leaf number and favored collar diameter, without a significant effect on total height. Fertilization with 21.6 mM NO3 − stimulated seedling growth, yielding the highest seedlings with the highest node number with leaves and the lowest percentage of nodulated plants. Seedlings from La Paz showed better response in collar diameter and leaf number than those from Campo Durán.